Development of a semantic and syntactic model of natural language by means of non-negative matrix and tensor factorization - Marchenko, O.O. (PROBLEMS IN PROGRAMMING, 2025)
A method of developing a structural model of natural language syntax and semantics is proposed. Syntactic and semantic relations between parts of a sentence are presented in a form of a recursive structure called a control space. Numerical characteristics of these data are stored in multidimensional arrays. After factorization, the arrays serve as the basis for the development of procedures for natural language semantic and syntactic analyses. Prombles in programming 2014; 2-3: 263-272